Advances in ergonomics of manufacturing : managing the enterprise of the future : proceedings of the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA /: managing the enterprise of the future : proceedings of the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available